Congenital Heart Disease and Its Impact on the Development of Anastomotic Strictures after Reconstruction of Esophageal Atresia - Pernilla Stenström; Martin Salö; Magnus Anderberg; Einar Arnbjörnsson (Gastroenterology Research and Practice)
Background. The aim was to explore if severe congenital heart disease (CHD) influenced the need for dilatation of anastomotic strictures (AS) after the repair of esophageal atresia (EA). Methods. A retrospective case-control study was conducted examining AS in children with EA and Gross type C. The spectra of CHD and cardiac interventions were reviewed. The frequency of dilatations of AS during the first year following EA reconstruction was compared between children with and without severe CHD requiring cardiac surgery during their first year of life. Endoscopic signs of stricture were an indication for dilatation. Results. Included in the follow-up for AS were 94 patients who had EA reconstructions, of whom 10 (11%) children had severe CHD requiring surgery during the first year including 19 different cardiac interventions. In total, 38 patients needed dilatation of esophageal AS, distributed as six (60%) with severe CHD and 32 (38%) without severe CHD (p=0.31). Conclusion. Severe CHD was present in 11% of children with EA. Esophageal AS developed in 60% children with concomitant CHD, but although high, it did not reach statistical difference from children without CHD (38%).